ECONOMETRIC ASSESSMENT OF THE EFFECT OF INVESTMENTS ON THE VOLUME OF CONSTRUCTION PRODUCTION (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, a regression analysis of the impact of investments on the volume of construction production was carried out. Conclusions about short-term and long-term changes were made by creating an autoregression model.